Persepsi Pelaku UMKM Tentang Penyajian Laporan Keuangan Berbasis SAK-ETAP di Kabupaten Serdang Bedagai Perspektif Akuntansi Syariah - Mutiara Zain Dalimunthe; Nurlaila Nurlaila; Hendra Hermain (ITB AAS INDONESIA Surakarta, 2023)
Lack of knowledge regarding the preparation of financial reports and little understanding of how to present financial reports in accordance with accounting standards is one of the obstacles experienced by UMKM actors. However, these obstacles became the basis for conducting this research which intends to find out how UMKM actors perceive the presentation of SAK-ETAPbased financial reports in Serdang Bedagai Regency (In Sharia Accounting). Based on the results of the research that has been done, it can be concluded as follows: The recording and preparation of financial reports by UMKM actors is only limited to simple reports made in accordance with the understanding and needs of each UMKM manager. UMKM actors do not apply SAK-ETAP in compiling financial reports, because UMKM managers do not understand SAK-ETAP. The perpetrator considered that the recording carried out was clear and in accordance with the needs. This is because there is no socialization or training from the government or institutions related to the meaning of SAK ETAP and the importance of preparing financial reports in accordance with SAK ETAP. SAK-ETAP also has compatibility with existing financial records in sharia accounting.